Management of Candida glabrata infectious crystalline keratopathy with endophthalmitis following penetrating keratoplasty - Ritu Nagpal; Sunita Chaurasia; Joveeta Joseph; Mudit Tyagi; Padmaja Kumari Rani; Muralidhar Ramappa; Rikin Shah (Indian Journal of Ophthalmology, 2018)
A 33-year-old male underwent an optical keratoplasty elsewhere in the right eye following which he developed endophthalmitis and subsequently underwent a pars plana vitrectomy and lensectomy. At presentation, he had a deep stromal crystalline infiltration along the graft–host junction. A large therapeutic keratoplasty was performed, and the excised corneal button was evaluated. Histopathology revealed gram-positive round-to-oval budding structures and microbiology identified the organism as Candida glabrata. He was treated with antifungals in the postoperative period. At 4 months after therapeutic keratoplasty, the patient developed recurrent endophthalmitis, following stoppage of antifungals. The treatment was reinstituted for another year, and the patient did well with a clear graft at 18-month-follow-up period after the recurrence episode. Management of infectious crystalline keratopathy with endophthalmitis is a challenging situation and requires long-term treatment.